1991
DOI: 10.1038/bjc.1991.418
|View full text |Cite
|
Sign up to set email alerts
|

Loss of monomorphic and polymorphic HLA antigens in metastatic breast and colon carcinoma

Abstract: Summary MHC class I antigens are intimately involved in intercellular communication, and recognition by cytotoxic T cells. Thus tumour cells that fail to express them may be at a growth or metastatic advantage. A series of ten colorectal and ten breast carcinomas, and their respective lymph node metastases, were examined immunohistologically using monoclonal antibodies (mAb) against both monomorphic and A2 polymorphic determinants, and beta-2-microglobulin (beta 2m). Four (Benacerraf, 1981;Linsk & Goodenow,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
1
1

Year Published

1993
1993
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 20 publications
(25 reference statements)
1
20
1
1
Order By: Relevance
“…Previous studies have shown that some MHC class I genes are not expressed in certain cancers, which may alter the immune response [20][21][22]. Altered expression of MHC, class I and II molecules has been described in metastatic lesions from breast tumors [23][24][25] and breast cancer lines [26].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that some MHC class I genes are not expressed in certain cancers, which may alter the immune response [20][21][22]. Altered expression of MHC, class I and II molecules has been described in metastatic lesions from breast tumors [23][24][25] and breast cancer lines [26].…”
Section: Discussionmentioning
confidence: 99%
“…Tumors evade immune recognition through various mechanisms, such as alteration of the tumor microenvironment or changes in MHC-I expression. Reduced or complete loss of MHC-I expression has been seen in a wide array of human cancers, including colorectal (13,14), breast (13,15), bladder (16), ovarian (17), and cervical carcinoma (18), suggesting the presence of immunoediting.…”
Section: Introductionmentioning
confidence: 99%
“…The cell killing actions of the adaptive immune response can be mitigated by the decreased expression of MHC molecules on cancer cells. [26][27][28] A more general resistance to immune cell killing may also be achieved by the increased expression of anti-apoptotic proteins, such as survivin and other IAPs, by cancer cells. 29,30 To obtain insight into cellular pathways that are associated with an increased resistance to immune cells, we screened a compound library for agents that sensitize colon cancer cells to TNF induced apoptosis, without affecting cell viability on their own.…”
Section: Introductionmentioning
confidence: 99%